Constrained intervals and interval spaces - Lodwick, Weldon A. [UNESP]; Jenkins, Oscar A. (Springer Nature, 2013)
Constrained intervals, intervals as a mapping from [0, 1] to polynomials of degree one (linear functions) with non-negative slopes, and arithmetic on constrained intervals generate a space that turns out to be a cancellative abelian monoid albeit with a richer set of properties than the usual (standard) space of interval arithmetic. This means that not only do we have the classical embedding as developed by H. Radström, S. Markov, and the extension of E. Kaucher but the properties of these polynomials. We study the geometry of the embedding of intervals into a quasilinear space and some of the properties of the mapping of constrained intervals into a space of polynomials. It is assumed that the reader is familiar with the basic notions of interval arithmetic and interval analysis. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: (standard) interval arithmetic; Constrained interval arithmetic; Interval analysis; Interval spaces; Interval arithmetic; Linear functions; Non negatives; Quasi-linear; Soft computing; Software engineering; Polynomials